Sustainability and sustainable development values in creative practices among design undergraduates of Russia and Malaysia - Balamuralithara A/L Balakrishnan, Catherina Anak Ugap (Tanjung Malim, 2024)
Sustainability and sustainable development values in creative practices among design undergraduates of Russia and Malaysia by Balamuralithara A/L Balakrishnan, Catherina Anak Ugap